2018
DOI: 10.1002/eji.201847534
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 inhibitory peptide reduces dendritic cell migration to the lymph nodes to control Th2 adaptive immunity in the mouse lung

Abstract: Type 2 immunity in the lung is promoted through the release of innate cytokines, including TSLP, from lung structural cells. These cytokines drive Type 2 immunity in part through upregulation of OX40L on dendritic cells (DCs). DCs expressing OX40L are potent inducers of Th2 differentiation. We have shown previously that STAT6 inhibitory peptide (STAT6-IP), a cell penetrating peptide designed to inhibit the STAT6 transcription factor, reduces the induction of Th2 adaptive immunity in murine models of respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Data from several studies have shown that STAT6-IP reduces Th2-biased inflammatory responses in the lung (38, 59, 60). Our published and unpublished data provide support for STAT6-IP inhibition of responses in innate cells of the lung to control Th2 adaptive immunity (37, 38, 60). Our ongoing objectives are to clarify how STAT6-IP modulates the ability of IL-33 to interact with IL-13 and STAT6 to induce AAM differentiation and eosinophil activation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Data from several studies have shown that STAT6-IP reduces Th2-biased inflammatory responses in the lung (38, 59, 60). Our published and unpublished data provide support for STAT6-IP inhibition of responses in innate cells of the lung to control Th2 adaptive immunity (37, 38, 60). Our ongoing objectives are to clarify how STAT6-IP modulates the ability of IL-33 to interact with IL-13 and STAT6 to induce AAM differentiation and eosinophil activation.…”
Section: Discussionsupporting
confidence: 55%
“…To assess lung function, mice were anesthetized using xylazine and sodium pentobarbital and paralyzed with pancuronium bromide. Total lung elastance and resistance in response to increasing doses of methacholine was measured as previously described (37, 38). Briefly, anesthetized and paralyzed mice were attached to a computer-controlled small-animal ventilator (flexiVent; Scireq, Montréal, QC, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…The DCs expressing OX40L are an inducer of Th2 differentiation in asthma. 30 , 31 OX40L affects the regulation of DCs to Th2 cells differentiation in asthma. Hence, we thought that exploring the expression mechanism of OX40L in DCs is very meaningful for understanding the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%